Coexistence of bullous pemphigoid, intrahepatic cholangiocarcinoma, and alopecia areata: a case report of multifactorial autoimmunity in a surgical context - Li, Shanlin; Wang, Ying; Yang, Dingquan (Frontiers in Immunology, 2025)
BackgroundBullous Pemphigoid (BP) is caused by a predominantly Th2-mediated attack on the basement membrane by the production of anti-BP180 and anti-BP230 antibodies. Malignant tumors can exacerbate immune disorders through a variety of potential pathways, including pro-inflammatory responses in the tumor microenvironment, cross-immune responses induced by tumor-associated antigens, and the lifting of immunosuppressive states and activation of underlying autoimmune responses after surgery. Alopecia Areata (AA) is an autoimmune disease caused by T-lymphocyte-mediated destruction of the immune privilege of the hair follicle, specifically involving the immune axes of Th1, Th2 and Th17. Both AA and BP are associated with dysregulation of cytokines such as IL-4, IL-13, and IL-17. However, the mechanisms underlying the coexistence of the three are unclear, and no cases of their combination have been reported.Case presentationA 67-year-old male patient presented to the clinic complaining of scattered erythema and blisters on the trunk and extremities with marked itching for 4 days. Previously, the patient had undergone surgery for intrahepatic cholangiocarcinoma 10 days earlier. Furthermore, he had developed alopecia areata with the SALT 50 six months earlier and has recovered with white hairs. By combining the patient’s history with his laboratory tests and pathologic examinations, the patient was diagnosed with bullous pemphigoid, intrahepatic cholangiocarcinoma, and alopecia areata. The patient demonstrated normalization of serum tumor markers post-resection of intrahepatic cholangiocarcinoma. Bullous pemphigoid lesions resolved completely with dupilumab-targeted therapy, while alopecia areata exhibited spontaneous remission with full hair regrowth despite no disease-specific treatment.ConclusionThis case report is the first to present the coexistence of bullous pemphigoid, malignant tumors, and alopecia areata, especially since the patient did not undergo immune medication, such as chemotherapy, which has implications for clinical confrontation with the combined presence of these diseases.